2019
DOI: 10.1080/14992027.2018.1534007
|View full text |Cite
|
Sign up to set email alerts
|

Beyond motivation: identifying targets for intervention to increase hearing aid use in adults

Abstract: Objective: The present study investigated: (a) how motivated patients are to use their hearing aid, and (b) whether post-motivational variables (e.g. action planning, coping planning) have anything to offer in terms of developing interventions to boost hearing aid use. Design: participants completed a questionnaire designed to tap Health Action Process Approach constructs prior to their hearing aid prescription and fitting. Study sample: Sixty-seven patients attending NHS audiology clinics. Results: Participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 36 publications
1
13
0
Order By: Relevance
“…The very high uptake of hearing aids may be because individuals sufficiently motivated to attend a hearing assessment may be likely to follow the advice of a hearing health care professional to obtain a hearing aid following a hearing assessment ( Armitage et al 2017 ). A high level of motivation to use hearing aids in individuals attending audiological clinics has been demonstrated in previous studies ( Meister et al 2008 , 2014 ; Ferguson et al 2016 ; Armitage et al 2017 ; Sawyer et al 2019b ).…”
Section: Discussionsupporting
confidence: 52%
“…The very high uptake of hearing aids may be because individuals sufficiently motivated to attend a hearing assessment may be likely to follow the advice of a hearing health care professional to obtain a hearing aid following a hearing assessment ( Armitage et al 2017 ). A high level of motivation to use hearing aids in individuals attending audiological clinics has been demonstrated in previous studies ( Meister et al 2008 , 2014 ; Ferguson et al 2016 ; Armitage et al 2017 ; Sawyer et al 2019b ).…”
Section: Discussionsupporting
confidence: 52%
“…There were no significant differences between non-regular and regular hearing aid users in other baseline characteristics in this study, but previous studies showed that adult patients who had a lower income ( Lupsakko et al., 2005 ) and who did not perceive a need for a hearing aid ( Lupsakko et al., 2005 ; Solheim et al., 2018 ) were more likely not to use or under use their hearing aids. Other factors that might predict low hearing aid use, for example, personality traits and coping strategies ( Cox et al., 2005 ) or postmotivational variables (e.g., action planning; Sawyer et al., 2019 ). Combinations of demographic and/or psychological variables could be used to identify those who are likely not to use hearing aids and may benefit from interventions to promote hearing aid use.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies report that 5% to 24% of hearing aid owners do not use their hearing aids ( Aazh et al., 2015 ; Hartley et al., 2010 ; Hougaard & Ruf, 2011 ; Solheim & Hickson, 2017 ) and 40% of new adult patients use their hearing aids fewer than 4 hours per day ( Aazh et al., 2015 ). A recent study reported that adult patients were highly motivated to use their hearing aids but had difficulty translating motivation into action (i.e., “volitional processes”; Sawyer et al., 2019 ). This suggests that interventions should target “volitional processes” (e.g., action planning) to increase hearing aid use among adult patients ( Sawyer et al., 2019 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…One key reason for non- and under-hearing aid use includes forgetting to use hearing aids ( McCormack & Fortnum, 2013 ). Forgetting to use hearing aids may be a result of patients not making explicit plans for hearing aid use ( Sawyer et al 2019 ). A Cochrane systematic review of intervention studies to promote hearing aid use found no self-management support and/or service delivery interventions in audiology that were effective in promoting hearing aid use in adults ( Barker et al 2016c ).…”
Section: Introductionmentioning
confidence: 99%